MATHMASTER: An alternative math word problems translation - Wanintorn Supap (2018)
We proposed the MATHMASTER approach that was designed to help students to gradually develop their skills required in solving math word problems. MATHMASTER automatically performs the translation from math word problem into an appropriate equation by taking into account the relationship between natural language and math concepts both in structure and semantics. The MATHMASTER system was implemented based on the MATHMASTER approach to translate word problems collected from many published mathematics practice books and primary school textbooks. MATHMASTER was designed to support individual learning and understanding of word problem solving through step by step instructions. Students can practice word problem solving at their own pace and enhance their word problem solving skill. The MATHMASTER system was tested and evaluated in terms of translation accuracy, usability of MATHMASTER in education, and user satisfaction. The evaluation results show that the translation accuracy is acceptable, MATHMASTER can be used to facilitate student's learning, and it satisfies the users' needs. © 2013 The authors and IOS Press. All rights reserved.